2021
DOI: 10.1038/s41467-021-22798-6
|View full text |Cite
|
Sign up to set email alerts
|

Breathing-driven prefrontal oscillations regulate maintenance of conditioned-fear evoked freezing independently of initiation

Abstract: Brain–body interactions are thought to be essential in emotions but their physiological basis remains poorly understood. In mice, regular 4 Hz breathing appears during freezing after cue-fear conditioning. Here we show that the olfactory bulb (OB) transmits this rhythm to the dorsomedial prefrontal cortex (dmPFC) where it organizes neural activity. Reduction of the respiratory-related 4 Hz oscillation, via bulbectomy or optogenetic perturbation of the OB, reduces freezing. Behavioural modelling shows that this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
96
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(124 citation statements)
references
References 78 publications
15
96
0
Order By: Relevance
“…Our results add to the increasing recognition of internally generated bodily influences as modulators of brain activity and cognitive functions, including drive from respiration, heart rate and gastrointestinal rhythms (Heck et al, 2019, Azzalini et al, 2019. RROs have been directly observed in various areas of the neocortex, hippocampus, thalamus, and amygdala (Zhong et al, 2017, Ito et al, 2014, Biskamp et al, 2017, Nguyen Chi et al, 2016, Lockmann et al, 2016, Moberly et al, 2018, Jung et al, 2019, Bagur et al, 2021 and are thought to impact cortical circuits through the entrainment of brain oscillations involved in cognitive functions, including theta (Zelano et al, 2016), gamma (Zhong et al, 2017, Biskamp et al, 2017 and sharp-wave/ripple oscillations (Liu et al, 2017). Based on our results we propose that the role of RROs extends to the building blocks of cortical computations, the assemblies.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our results add to the increasing recognition of internally generated bodily influences as modulators of brain activity and cognitive functions, including drive from respiration, heart rate and gastrointestinal rhythms (Heck et al, 2019, Azzalini et al, 2019. RROs have been directly observed in various areas of the neocortex, hippocampus, thalamus, and amygdala (Zhong et al, 2017, Ito et al, 2014, Biskamp et al, 2017, Nguyen Chi et al, 2016, Lockmann et al, 2016, Moberly et al, 2018, Jung et al, 2019, Bagur et al, 2021 and are thought to impact cortical circuits through the entrainment of brain oscillations involved in cognitive functions, including theta (Zelano et al, 2016), gamma (Zhong et al, 2017, Biskamp et al, 2017 and sharp-wave/ripple oscillations (Liu et al, 2017). Based on our results we propose that the role of RROs extends to the building blocks of cortical computations, the assemblies.…”
Section: Discussionsupporting
confidence: 57%
“…Nasal airflow activates olfactory sensory neurons in the olfactory epithelium (Grosmaitre et al, 2007), thereby producing oscillating depolarizations that are broadcast to the brain via the olfactory bulbs (Fontanini and Bower, 2006). Besides the well-studied role of respiration-related oscillations (RROs) in the processing of olfactory information (Kay, 2015), converging evidences indicate that RROs occurs in a variety of higher-order cortical areas including the medial prefrontal cortex (mPFC, Biskamp et al, 2017, Nguyen Chi et al, 2016, Lockmann et al, 2016, Ito et al, 2014, Zhong et al, 2017, Karalis and Sirota, 2018, Moberly et al, 2018, Kőszeghy et al, 2018, Bagur et al, 2021). These results suggest that rhythmic breathing might affect cognitive functions beyond the processing of smells (Heck et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has identified the dorsomedial mPFC, comprised largely of the prelimbic cortex, as an important site for conditioned stimulus (CS) processing in auditory fear conditioning and a critical substrate for fear expression (Bagur et al, 2021; Burgos-Robles et al, 2009; Corcoran and Quirk, 2007; Courtin et al , 2014; Cummings and Clem, 2020; Dejean et al, 2016; DeNardo et al, 2019; Herry and Johansen, 2014; Karalis et al, 2016; Sotres-Bayon and Quirk, 2010; Xu et al , 2019). To identify neurons selectively recruited by learning in the prelimbic mPFC, we employed a viral genetic approach to permanently tag these cells with a fluorescent reporter.…”
Section: Resultsmentioning
confidence: 99%
“…First, local neurons are modulated by ongoing RR. Both neocortical and hippocampal neurons discharge phase-coupled to RR (Yanovsky et al, 2014 ; Biskamp et al, 2017 ; Karalis and Sirota, 2018 ; Moberly et al, 2018 ; Bagur et al, 2021 ), and whole-cell recordings indicated respiration-synchronous subthreshold membrane oscillations in pyramidal neurons, initially in the piriform cortex (Fontanini et al, 2003 ) and more recently in the parietal cortex (Jung et al, 2019 ). Notably, these subthreshold oscillations are reduced when airflow through the nose is prevented by tracheotomy (Fontanini et al, 2003 ), further supporting the causal role of nasal airflow for cortical RRs.…”
Section: Mechanisms Of Generation Of Respiration-driven Brain Oscillationsmentioning
confidence: 99%
“…Further experiments revealed that these oscillations are propagated to olfactory areas such as the piriform cortex, giving rise to the hypothesis that respiration-synchronous oscillations might aid the processing of olfactory inputs (Fontanini and Bower, 2006 ). In recent years, an increasing number of studies additionally reported respiration-synchronous brain oscillations in various brain regions, including higher-order areas involved in cognitive functions ( Figure 1 ; Ito et al, 2014 ; Lockmann et al, 2016 ; Nguyen Chi et al, 2016 ; Biskamp et al, 2017 ; Zhong et al, 2017 ; Karalis and Sirota, 2018 ; Moberly et al, 2018 ; Bagur et al, 2021 ). These data suggest that respiration-related oscillations [also called respiration rhythms (RRs)] might fulfill general functions in neuronal circuits that extend beyond the processing of olfactory inputs.…”
Section: Introductionmentioning
confidence: 99%